(untitled) (Journal of the College of Basic Education, 2026)
This study aimed to explore the most prevalent measurement and evaluation methods for enhancing the quality of scientific research, identify challenges encountered in multidisciplinary research, and propose improvement strategies. The study adopted a mixed-methods approach, utilizing a sequential explanatory design. Quantitative data were initially collected using a scale from a sample of 350 researchers from various scientific disciplines, selected via stratified random sampling. Subsequently, qualitative data were gathered through semi-structured interviews with 15 purposively selected experienced researchers. The findings revealed an 80% effectiveness rate for the use of quantitative measures in scientific research, and statistical analysis was deemed important in study outcomes by 70% of respondents, with these being the most frequently utilized approaches, exhibiting variations across disciplines. A strong positive relationship was identified between the quality of measurement and evaluation methods and validity (β = 0.65), explaining 42% of the variance (R² = 0.42). Furthermore, this quality significantly influenced reliability (β = 0.61), accounting for 37% of its variance (R² = 0.37). Key challenges identified included difficulties in standardizing tools, a lack of technical skills, the complexity of multidisciplinary phenomena, and scarce resources, and Researchers’ suggestions included developing specialized training, employing advanced technologies, designing flexible tools, and fostering collaboration among researchers. The study recommended enhancing capabilities through advanced training programs, leveraging contemporary technologies to improve the efficiency of research tools, developing flexible tools adaptable to multidisciplinarity, and encouraging research partnerships to foster integration. Further recommendations include providing institutional support to overcome material obstacles, establishing standardized evaluation criteria across disciplines, conducting future research to explore practical applications, and promoting awareness of the importance of psychometric properties.